Screening and bioinformatics analysis of IgA nephropathy gene based upon GEO database - Liu Yin; Zhao Bin; Xie Yu-sai; Yang Tao (Linchuang shenzangbing zazhi)
Objective To identify novel biomarkers of IgA nephropathy（IgAN）through bioinformatics analysis and elucidate the possible molecular mechanism of IgAN.Methods The microarray datasets of GSE104948,GSE93798 and GSE37460 containing IgAN patients and healthy controls were downloaded from the GEO database and analyzed by using the limma R package for obtaining differentially expressed genes.Then GO and KEGG pathway enrichment analyses were performed.And STRING and Cytoscape software were utilized for constructing protein interaction networks for elucidating the molecular mechanism of IgAN.Results Thirty DEGs were identified, including 16 up-regulated genes and 14 down-regulated genes.Up-regulated genes such as FN1 and COL1 A2 are mainly involved in extracellular matrix receptor interaction and PI3 K-Akt signaling pathway.ALB gene was significantly down-regulated in IgA nephropathy.And FN1,COL1 A2,ALB and FABP genes were screened as hub genes.Conclusion FN1,COL1 A2,ALB and FABP genes may play an important role in the development of IgA nephropathy and serve as potential molecular targets for diagnosing and treating IgAN.